2000
DOI: 10.1086/303055
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Genes Involved in Folate Metabolism as Maternal Risk Factors for Down Syndrome

Abstract: Down syndrome is a complex genetic and metabolic disorder attributed to the presence of three copies of chromosome 21. The extra chromosome derives from the mother in 93% of cases and is due to abnormal chromosome segregation during meiosis (nondisjunction). Except for advanced age at conception, maternal risk factors for meiotic nondisjunction are not well established. A recent preliminary study suggested that abnormal folate metabolism and the 677C-->T polymorphism in the methylenetetrahydrofolate reductase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
262
4
5

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(286 citation statements)
references
References 57 publications
15
262
4
5
Order By: Relevance
“…41 There is also evidence emerging that there is an association between folate and Down syndrome. 42,43 This genetic predisposition may therefore play a significant role in public health in the not too distant future, if and when screening for it becomes feasible and acceptable in the wider community. Not only may we be able to prevent specific birth defects from forming, but there may also be opportunities to identify those at higher risk of common disorders in adult life.…”
Section: Discussionmentioning
confidence: 99%
“…41 There is also evidence emerging that there is an association between folate and Down syndrome. 42,43 This genetic predisposition may therefore play a significant role in public health in the not too distant future, if and when screening for it becomes feasible and acceptable in the wider community. Not only may we be able to prevent specific birth defects from forming, but there may also be opportunities to identify those at higher risk of common disorders in adult life.…”
Section: Discussionmentioning
confidence: 99%
“…Down syndrome, an important condition leading to mental retardation, has been associated with polymorphisms in genes involved in folate metabolism (James et al, 1999;Hobbs et al, 2000). One gene variant in particular, the C677T/C677T genotype, of the 5,10 methylenetetrahydrofolate reductase (MTHFR) gene, has been associated with Down syndrome as well as being a risk factor for other complex congenital anomalies (Botto and Yang, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Frosst et al (1995) identified a C to T substitution at nucleotide 677 in the coding region of the MTHFR gene converting an alanine to a valine residue in the gene product and creating a new HinfI restriction site resulting in the MTHFR 677C ® T polymorphism and a reduction in enzyme activity which may lead to a decrease in the levels of SAM, inhibition of methyltransferase and subsequent DNA hypomethylation. The importance of the stable methylation of pericentromeric DNA for chromosomal stabilization and segregation has been supported both by clinical and experimental data (reviewed by Hobbs et al, 2000). Therefore, in homozygosis, the 677C ® T mutation may be a contributing risk factor to somatic chromosomal non-disjunction.…”
mentioning
confidence: 99%
“…Defects in folic acid metabolism because of mutations in the 5,10-methylenetetrahydrofolate reductase (MTHFR) gene have been considered as a possible cause of chromosomal non-disjunction by hypomethylation (James et al, 1999;Hobbs et al, 2000). The MTHFR gene is located on the short arm of chromosome 1 (1p36.3) and has 11 exons (Goyette et al, 1994) which code for a cytosolic flavoprotein that catalyzes the reduction of 5,10-methylenetetrahydrofolate (5,10-methyleneTHF) to 5-methyltetrahydrofolate (5-methylTHF), the predominant circulating form of folic acid (Weisberg et al, 1998).…”
mentioning
confidence: 99%